A polyvinyl chloride functional filler modification treatment method
Patent Information
- Application Number
- CN202611411486.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]针对现有纯聚氯乙烯作为橡胶基摩擦材料填料时,因分子链缺乏化学反应活性及相容性缺陷,导致在高温剪切环境下易发生界面微相分离、介质溶胀和磨粒剥落的技术缺陷,本发明的目的在于提供一种聚氯乙烯功能性填料改性处理方法;具体地,本发明技术方案如下:
通过原位构建化学互穿网络,将改性聚氯乙烯从惰性调节组分转化为增强相;材料的层间剪切强度提升40%以上;在湿式摩擦磨损试验中,磨损率较传统纯聚氯乙烯体系降低35%-50%;得益于羧基和酯基的协同增容与交联作用,改性聚氯乙烯的添加量可由传统的5-10wt%提升至15-45wt%,不仅有效调节了摩擦片的综合摩擦性能,还显著提升了该填料在橡胶基体中的最大有效填充质量分数;在油介质中浸泡测试后,本发明材料的体积膨胀率控制在1.5%至2.0%的范围内,质量变化率控制在0.7%至1.0%的范围内,满足湿式传动环境的应用技术指标。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer composite friction materials technology, specifically a method for modifying polyvinyl chloride functional fillers. Background Technology
[0002] In wet clutches and gearboxes, rubber-based friction materials are widely used due to their good elasticity and stable coefficient of friction. Polyvinyl chloride (PVC) has excellent chemical resistance, flame retardancy and low cost advantages, and is often added to rubber-based friction materials as a hard modifier. However, in the prior art, the amount of pure PVC added as an inert filler is usually limited to 5-10 wt%. Because pure polyvinyl chloride (PVC) molecular chains lack reactivity, they only have weak van der Waals forces and physical-mechanical interlocking with the rubber matrix, and cannot form chemical bonds. This compatibility defect leads to interfacial microphase separation, media swelling, and abrasive grain shearing of friction materials under the high-temperature shearing environment of wet transmission fluid. This not only limits the realization of high PVC filling capacity, but also makes it difficult for the wear life and corrosion resistance of friction materials to meet the requirements of modern high-power-density transmission systems. Summary of the Invention
[0003] To address the shortcomings of existing pure polyvinyl chloride (PVC) fillers used as rubber-based friction materials, such as the lack of chemical reactivity and compatibility of the molecular chains leading to interfacial microphase separation, media swelling, and abrasive particle delamination under high-temperature shear conditions, this invention aims to provide a method for modifying PVC functional fillers. Specifically, the technical solution of this invention is as follows: A method for modifying polyvinyl chloride (PVC) with functional fillers includes the following steps: Deionized water and polyvinyl alcohol were mixed, and inorganic acid was added dropwise to adjust the pH of the aqueous phase to 5.0-7.0 to obtain a dispersion. Vinyl chloride monomer, ester-containing monomer, carboxyl-containing monomer and initiator are added sequentially to the dispersion, wherein the ester-containing monomer accounts for 5-15 mol% of the total molar amount of monomers, the carboxyl-containing monomer accounts for 1-5% of the total molar amount of monomers, and the remainder is vinyl chloride monomer. The amount of initiator is 0.05-0.5 mol% of the total mass of monomers. Under stirring conditions, the suspension polymerization reaction is carried out at 55-65°C for 6-10 hours. After the reaction was completed, the product underwent degassing, centrifugal washing, and fluidized bed drying processes in sequence to obtain the modified polyvinyl chloride functional filler.
[0004] Preferably, the inorganic acid is hydrochloric acid; the ester-containing monomer is vinyl acetate or butyl acrylate; the carboxyl-containing monomer is methacrylic acid or acrylic acid; and the initiator is diisopropyl peroxide.
[0005] Preferably, in the molecular chain of the modified polyvinyl chloride functional filler, the molar content of carboxyl groups is 1-5 mol%, and the molar content of ester groups is 5-15 mol%; the average particle size of the modified polyvinyl chloride functional filler is 50-150 μm.
[0006] Preferably, the modification method further includes a step of compounding the modified polyvinyl chloride functional filler with a rubber matrix: Solid multifunctional epoxy resin and the first part of the friction performance modifier were premixed at a mass ratio of 1:(1-3) at a speed of 500-1500 rpm to obtain powdered bridging masterbatch. The rubber matrix is subjected to roll plasticizing treatment on an open rubber mixing mill. The modified polyvinyl chloride functional filler, the second part of the friction performance modifier and the powdered bridging masterbatch are added in sequence for mixing and pre-activation treatment. After the filler is evenly dispersed, the vulcanization crosslinking system and epoxy ring-opening catalyst are added. The mixing temperature is controlled between 80-100℃, and the mixture is sheeted to obtain the compound rubber. The compounded rubber is placed in a mold for hot-press cross-linking molding, which causes the rubber matrix to vulcanize. The active groups in the modified polyvinyl chloride functional filler undergo cross-linking reaction with the rubber matrix and / or the interpenetrating network bridging system composed of the solid multifunctional epoxy resin and the epoxy ring-opening catalyst to construct a chemical interpenetrating network structure, thereby obtaining a friction pad. The friction pads are subjected to post-vulcanization and heat preservation treatment to obtain a rubber-based wet friction material based on a modified polyvinyl chloride interpenetrating network structure; wherein, the friction performance modifier includes fiber reinforcement material and mineral filler; the first part of the friction performance modifier is a portion of the mineral filler, accounting for 15%-30% of the total mineral filler mass; the second part of the friction performance modifier is the fiber reinforcement material and the remaining mineral filler.
[0007] Preferably, the premixing treatment is carried out in a high-speed mixer; the hot-press cross-linking molding treatment is performed at 150-180℃ and 10-20MPa for 5-15 minutes; the post-vulcanization heat preservation treatment is performed at 160℃ for 2-4 hours.
[0008] Preferably, the compound comprises the following components by weight: the rubber matrix: 100 parts; the modified polyvinyl chloride functional filler: 15-45 parts; the vulcanization crosslinking system: 3-8 parts; Interpenetrating network bridging system: 2-6 parts, wherein the interpenetrating network bridging system is composed of the solid multifunctional epoxy resin and the epoxy ring-opening catalyst in a mass ratio of (10-20):1; Friction performance modifier: 40-80 parts, wherein the friction performance modifier is composed of the first part of the friction performance modifier and the second part of the friction performance modifier.
[0009] Preferably, the rubber matrix is nitrile rubber or carboxylated nitrile rubber; the vulcanization crosslinking system includes sulfur, rubber accelerator and zinc oxide.
[0010] Preferably, the solid multifunctional epoxy resin is a solid bisphenol A type epoxy resin or an o-cresol formaldehyde type epoxy resin; the epoxy ring-opening catalyst is an imidazole derivative or a quaternary ammonium salt.
[0011] The beneficial effects of this invention are as follows: By constructing an in-situ chemical interpenetrating network, modified polyvinyl chloride (PVC) is transformed from an inert regulating component into a reinforcing phase; the interlaminar shear strength of the material is increased by more than 40%; in wet tribology tests, the wear rate is reduced by 35%-50% compared to the traditional pure PVC system; thanks to the synergistic compatibilization and crosslinking effect of carboxyl and ester groups, the amount of modified PVC added can be increased from the traditional 5-10 wt% to 15-45 wt%, which not only effectively regulates the comprehensive tribological performance of the friction pad, but also significantly increases the maximum effective filler mass fraction of the filler in the rubber matrix; after immersion testing in oil medium, the volume expansion rate of the material of this invention is controlled within the range of 1.5% to 2.0%, and the mass change rate is controlled within the range of 0.7% to 1.0%, meeting the application technical indicators for wet transmission environments. Detailed Implementation
[0012] The technical solutions in the embodiments of the present invention will be clearly and completely described below; the described embodiments are some embodiments of the present invention, but not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention. Example 1
[0013] This embodiment provides a rubber-based wet friction material, specifically including the following steps: S1. Preparation of modified polyvinyl chloride functional filler: 1000g of deionized water and 2.5g of polyvinyl alcohol were added to a reaction vessel and mixed. Hydrochloric acid was added dropwise to adjust the pH of the aqueous phase to 5.5 to obtain a dispersion. Vinyl chloride monomer, vinyl acetate and methacrylic acid were added to the dispersion. The total mass of the monomers was 500g, of which vinyl acetate accounted for 10% of the total molar mass of the monomers, methacrylic acid accounted for 3% of the total molar mass of the monomers, and the remainder was vinyl chloride monomer. Diisopropyl peroxide dicarbonate was added, and the initiator dosage was 0.2% of the total monomer mass. Suspension polymerization was carried out at 60°C for 8 hours under stirring. After the reaction, degassing, centrifugal washing, and fluidized bed drying were performed to obtain modified polyvinyl chloride functional filler with an average particle size of 80 μm. The monomer conversion rate of the copolymerization reaction was determined to be 92%, and the product yield was 90%. The final modified polyvinyl chloride functional filler molecular chain contained 2.8 mol% carboxyl groups and 9.5 mol% ester groups. S2. Preparation of powdered bridging masterbatch: 3 parts of solid bisphenol A type epoxy resin and 9 parts of precipitated barium sulfate were added to a high-speed mixer and premixed at a speed of 1000 rpm. The mass ratio of epoxy resin to this part of mineral filler was 1:3 to obtain powdered bridging masterbatch. S3. Pre-activation of compounding: By mass, take 100 parts of nitrile rubber, 25 parts of modified polyvinyl chloride functional filler obtained in step S1, 10 parts of aramid pulp, 20 parts of precipitated barium sulfate, 24 parts of flake graphite, and all the powdered bridging masterbatch obtained in step S2, totaling 12 parts, and mix them on an open rubber mixing mill; the rubber matrix is first plasticized by roller wrapping, and then the modified polyvinyl chloride functional filler, aramid pulp, remaining precipitated barium sulfate, flake graphite, and powdered bridging masterbatch are added in sequence; after the filler is evenly dispersed, add 5 parts of zinc oxide, 1.5 parts of accelerator N-cyclohexyl-2-benzothiazole sulfenamide, 1.5 parts of sulfur, and 0.3 parts of 2-methylimidazole, control the mixing temperature at 90℃, and sheet out to obtain the compounded rubber; S4. Hot-press cross-linking molding and post-vulcanization: After the compounded rubber is left to stand, it is cut and placed into a mold. It is then hot-pressed and vulcanized at 165℃ and 15MPa for 10 minutes to obtain a friction pad. Then, it is kept at 160℃ for 3 hours to obtain the target wet friction material. In this embodiment, the proportions of modified polyvinyl chloride functional filler, carboxyl and ester monomer content, bridging system dosage, and hot pressing conditions are kept within a certain range. The resulting material achieves stable chemical cross-linking at the interface, and the interlaminar shear strength and media resistance reach optimal values. Example 2
[0014] This embodiment provides a rubber-based wet friction material, specifically including the following steps: S1. Preparation of modified polyvinyl chloride functional filler: Mix 1000g of deionized water with 2.0g of polyvinyl alcohol, and adjust the pH of the aqueous phase to 6.5 by adding hydrochloric acid dropwise; add vinyl chloride monomer, vinyl acetate and methacrylic acid to the system, with a total monomer mass of 500g, of which vinyl acetate accounts for 5% of the total molar mass of monomer, methacrylic acid accounts for 1% of the total molar mass of monomer, and the remainder is vinyl chloride monomer; add diisopropyl peroxide, and the amount of initiator is 0.1% of the total monomer mass; The suspension polymerization reaction was carried out at 55℃ for 6 hours. After the reaction, the product was degassed, centrifuged, washed, and boiled dry to obtain a modified polyvinyl chloride functional filler with an average particle size of 150 μm. The monomer conversion rate of the copolymerization reaction was 95%, and the product yield was 93%. The final modified polyvinyl chloride functional filler had a molar content of 1.0 mol% for carboxyl groups and 5.0 mol% for ester groups in its molecular chain. S2. Preparation of powdered bridging masterbatch: 2.0 parts of solid bisphenol A epoxy resin and 6 parts of wollastonite were added to a high-speed mixer and premixed at a speed of 500 rpm to obtain powdered bridging masterbatch. S3. Pre-activation of compounding: By mass, take 100 parts of nitrile rubber, 15 parts of the modified polyvinyl chloride functional filler obtained in step S1, 12 parts of aramid pulp, 20 parts of wollastonite, 12 parts of flake graphite, and all the powdered bridging masterbatch obtained in step S2, totaling 8 parts, and mix them. After the filler is evenly dispersed, add 4.0 parts of zinc oxide, 1.2 parts of accelerator N-cyclohexyl-2-benzothiazole sulfenamide, 1.0 part of sulfur, and 0.2 parts of 2-methylimidazole. Control the mixing temperature at 80℃, and sheet out to obtain the compound. S4. Hot-press cross-linking molding and post-vulcanization: Place the compounded rubber in a mold and hot-press vulcanize it for 5 minutes at 150℃ and 10MPa; then keep it at 160℃ for 2 hours to obtain the target material. This embodiment uses a low-value combination within the protection range. The amount of modified polyvinyl chloride introduced and the amount of bridging system used are at the lower limit of the set range, which can still form a certain degree of interfacial cross-linking structure, but the reinforcement and oil resistance effects are lower than those of Example 1. Example 3
[0015] This embodiment provides a rubber-based wet friction material, specifically including the following steps: S1. Preparation of modified polyvinyl chloride functional filler: 1000g of deionized water and 3.0g of polyvinyl alcohol were mixed, and hydrochloric acid was added dropwise to adjust the pH of the aqueous phase to 5.0; vinyl chloride monomer, butyl acrylate and acrylic acid were added to the system, with a total monomer mass of 500g, of which butyl acrylate accounted for 15% of the total molar mass of monomers, acrylic acid accounted for 5% of the total molar mass of monomers, and the remainder was vinyl chloride monomer; diisopropyl peroxide was added, and the amount of initiator was 0.4% of the total monomer mass; suspension polymerization was carried out at 65℃ for 10 hours. After the reaction was completed, degassing, centrifugal washing and boiling drying were performed in sequence to obtain modified polyvinyl chloride functional filler with an average particle size of 50μm; S2. Preparation of powdered bridging masterbatch: 5.5 parts of o-cresol formaldehyde solid epoxy resin and 16.5 parts of wollastonite were added to a high-speed mixer for premixing to obtain powdered bridging masterbatch; S3. Pre-activation of compounding: By mass, take 100 parts of carboxylated nitrile rubber, 45 parts of modified polyvinyl chloride functional filler obtained in step S1, 12 parts of carbon fiber, 18.5 parts of wollastonite, 20 parts of molybdenum disulfide, and all the powdered bridging masterbatch obtained in step S2, totaling 22 parts, and mix them. After the filler is evenly dispersed, add 5.5 parts of zinc oxide, 1.5 parts of accelerator tetramethylthiuram disulfide, 1.0 part of sulfur, and 0.5 parts of tetrabutylammonium bromide. Control the mixing temperature at 100℃, and sheet out to obtain the compound. S4. Hot-press cross-linking molding and post-vulcanization: The compound rubber is placed in a mold and hot-pressed and vulcanized at 175℃ and 18MPa for 12 minutes; then kept at 160℃ for 4 hours to obtain the target material. In this embodiment, the content of modified polyvinyl chloride functional filler and ester and carboxyl monomers is at a high level, and the polarity matching and cross-linking reaction ability of the material are strong. However, the high filler content will increase the rigidity of the system, resulting in a reduction in the range of operable temperature and pressure parameters during processing. Example 4
[0016] This embodiment provides a rubber-based wet friction material, specifically including the following steps: S1. Preparation of modified polyvinyl chloride functional filler: 1000g of deionized water and 2.5g of polyvinyl alcohol were mixed, and hydrochloric acid was added dropwise to adjust the pH of the aqueous phase to 6.0; vinyl chloride monomer, butyl acrylate and methacrylic acid were added to the system, with a total monomer mass of 500g, of which butyl acrylate accounted for 8% of the total molar mass of monomer, methacrylic acid accounted for 4% of the total molar mass of monomer, and the remainder was vinyl chloride monomer; diisopropyl peroxide was added, and the amount of initiator was 0.25% of the total monomer mass; suspension polymerization was carried out at 62℃ for 8 hours. After the reaction, degassing, centrifugal washing and boiling drying were performed in sequence to obtain modified polyvinyl chloride functional filler with an average particle size of 60μm; S2. Preparation of powdered bridging masterbatch: 4.0 parts of o-cresol formaldehyde solid epoxy resin and 12 parts of wollastonite were added to a high-speed mixer for premixing to obtain powdered bridging masterbatch; S3. Pre-activation of compounding: By mass, take 100 parts of carboxylated nitrile rubber, 35 parts of modified polyvinyl chloride functional filler obtained in step S1, 15 parts of carbon fiber, 28 parts of wollastonite, 20 parts of molybdenum disulfide, and all the powdered bridging masterbatch obtained in step S2, totaling 16 parts, and mix them. After the filler is evenly dispersed, add 5.0 parts of zinc oxide, 2.0 parts of accelerator tetramethylthiuram disulfide, 1.0 part of sulfur, and 0.4 parts of tetrabutylammonium bromide. Control the mixing temperature at 95℃, and sheet out to obtain the compound. S4. Hot-press cross-linking molding and post-vulcanization: The compound rubber is placed in a mold and hot-pressed and vulcanized at 170℃ and 12MPa for 12 minutes; then kept at 160℃ for 3 hours to obtain the target material. In this embodiment, the median parameter ratio within the protection range is used, and the dispersion state and bridging reaction of the modified polyvinyl chloride functional filler in the rubber are relatively stable, with overall performance close to that of Example 1.
[0017] Comparative Example 1: The difference between this comparative example and Example 1 is that the 25 parts of modified polyvinyl chloride functional filler in Example 1 are replaced with 25 parts of commercially available pure polyvinyl chloride resin powder, while the other operating steps and process parameters are exactly the same as in Example 1. Because pure polyvinyl chloride (PVC) molecules do not contain carboxyl and ester active groups, it is difficult to form an effective chemical bond with the rubber matrix and bridging system during hot-press vulcanization.
[0018] Comparative Example 2: The difference between this comparative example and Example 1 is that the solid bisphenol A epoxy resin and 2-methylimidazole in Example 1 are omitted, while the other operating steps and process parameters are exactly the same as in Example 1. This comparative example retains the modified polyvinyl chloride functional filler, but does not introduce an interpenetrating network bridging system.
[0019] Comparative Example 3: The difference between this comparative example and Example 1 is that the amount of modified polyvinyl chloride functional filler in Example 1 is adjusted from 25 parts to 8 parts, and the amount of precipitated barium sulfate is adjusted from 20 parts to 37 parts. Other operating steps and process parameters are exactly the same as in Example 1. This comparative example is used to investigate the effect of the amount of modified polyvinyl chloride added at the lower limit of the set range on the interfacial crosslinking structure and friction durability.
[0020] Comparative Example 4: The difference between this comparative example and Example 1 is that the pH value of the aqueous phase was adjusted from 5.5 to 2.5 during the preparation of the modified polyvinyl chloride functional filler, while the other operating steps and process parameters were exactly the same as in Example 1. This comparative example is used to investigate the effect of the pH value of the aqueous phase deviating from the range of the present invention during the suspension polymerization stage on the introduction effect of functional monomers and subsequent composite performance.
[0021] Comparative Example 5: The difference between this comparative example and Example 1 is that the post-vulcanization heat preservation treatment step is omitted, and the friction material is obtained directly after hot-press vulcanization. Other operation steps and process parameters are exactly the same as in Example 1. This comparative example is used to investigate the effect of post-vulcanization treatment on the completion of the epoxy ring-opening reaction and the stability of the material.
[0022] Performance Testing and Datasheets Interlaminar shear strength was determined according to GB / T1450; dynamic friction coefficient and wear rate were tested using MM-1000 friction and wear testing machine. The test conditions were: contact pressure 1.0MPa, rotation speed 2000rpm, test time 2 hours, and the test medium was DEXRON-VI automatic transmission fluid. The resistance to the medium was evaluated by the volume expansion rate and mass change rate after immersion in automatic transmission fluid at 150℃ for 500 hours. Characterized by Fourier transform infrared spectroscopy, dynamic thermomechanical analysis, and scanning electron microscopy, all samples in Examples 1 to 4 exhibited ester carbonyl groups, zinc carboxylate ionic bonds, and hydroxyl groups after epoxy ring opening. The phase interfaces in Examples 1 and 4 were relatively continuous, while Comparative Examples 1 and 2 showed obvious phase boundaries and particle detachment traces. The average particle size of the modified polyvinyl chloride functional filler was determined using a laser particle size analyzer. The monomer conversion rate and the molar content of each group in the copolymer were quantitatively determined using nuclear magnetic resonance spectroscopy or chemical titration. Table 1 Summary of performance test results for each embodiment and comparative example
[0023] As can be seen from the comparison of the test results of Example 1 and Comparative Example 1 in Table 1, after replacing the modified polyvinyl chloride functional filler with pure polyvinyl chloride resin powder, the interlaminar shear strength, dynamic friction coefficient and media resistance all decreased significantly. Pure polyvinyl chloride does not contain carboxyl groups and ester groups, making it difficult to form ionic bonds with zinc oxide and difficult to undergo ring-opening reactions with epoxy resin. The interface is mainly in physical contact. Under the combined action of automatic transmission oil and frictional shear, this interface is prone to forming micropores and producing particle pull-out phenomena, increasing the wear rate, volume expansion rate and mass change rate. As can be seen from the comparison of the test results of Example 1 and Comparative Example 2 in Table 1, after omitting the interpenetrating network bridging system, the interlaminar shear strength decreased from 12.8 MPa to 8.1 MPa, and the wear rate and oil resistance also deteriorated significantly. Although the modified polyvinyl chloride has carboxyl and ester groups, without multifunctional epoxy resin and ring-opening catalyst, the interface can only rely on limited ion coordination and polar interaction, making it difficult to form a relatively continuous chemical connection structure. When the interface is not tightly bonded, the friction surface is more prone to local peeling, and the oil medium is more likely to penetrate along the phase interface. As can be seen from the comparison of the test results of Example 1 and Comparative Example 3 in Table 1, when the amount of modified polyvinyl chloride functional filler added was reduced from 25 parts to 8 parts, the overall material performance decreased. The modified polyvinyl chloride not only provides a hardening effect in this system, but also participates in interfacial crosslinking and polar compatibilization. When the amount added is too low, the number of active phases that can participate in co-crosslinking decreases, the interfacial network density decreases, and the stable structure in the material that can withstand frictional loads decreases accordingly. Therefore, the interlaminar shear strength, frictional stability and wear resistance are all inferior to those of Example 1. As can be seen from the comparison of the test results of Example 1 and Comparative Example 4 in Table 1, after adjusting the pH value of the aqueous phase in the suspension polymerization stage from 5.5 to 2.5, the mechanical and media resistance properties of the obtained material both decreased. When the pH value of the aqueous phase deviated from the set range, the distribution state of the carboxyl-containing monomers changed during the polymerization process, and the degree of introduction of active groups in the modified polyvinyl chloride molecular chain and its distribution uniformity were affected. When the distribution of functional groups was unstable, it was difficult to maintain a high degree of consistency in the ionic crosslinking and epoxy ring-opening reaction in the subsequent hot pressing stage, the interface structure tended to be loose, and the barrier effect of the material on automatic transmission oil was also weakened. As can be seen from the comparison of the test results of Example 1 and Comparative Example 5 in Table 1, after omitting the post-vulcanization heat preservation treatment, the interlaminar shear strength, wear rate and oil resistance index all decreased; the rubber cross-linking and part of the epoxy ring-opening reaction have occurred in the hot-press vulcanization stage, but there are still unreacted epoxy groups and local internal stress; without the post-vulcanization treatment, the integrity of the interpenetrating network structure is insufficient, the chemical connection density of the interface region is at the lower limit of the set range, and the material is more prone to microcrack propagation and local softening under the action of oil medium and friction load, so the overall performance is lower than that of Example 1; Within the range of raw material composition and process conditions defined by this invention, the modified polyvinyl chloride functional filler, bridging system, vulcanization crosslinking system, and friction performance modifier have a good synergistic relationship. When the low-value combination is used in Example 2, the degree of interfacial reaction and the reinforcing effect of the filler are weakened. When the high-value combination is used in Example 3, although it still has good friction performance and media resistance, the higher filler content will increase the rigidity of the system, and the interlaminar shear strength is slightly lower than that in Example 1. When the intermediate parameter combination is used in Example 4, the overall performance is close to that of Example 1, indicating that the technical solution has a process applicability range covering the above parameter range.
[0024] The above are merely specific embodiments of the present invention and are not intended to limit the present invention in any other way. Any person skilled in the art may make changes or modifications to the above-disclosed technical content to create equivalent embodiments for application in other fields. However, any conventional modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the technical solution of the present invention shall still fall within the protection scope of the technical solution of the present invention.
Claims
1. A method for modifying polyvinyl chloride functional fillers, characterized in that, Includes the following steps: Deionized water and polyvinyl alcohol were mixed, and inorganic acid was added dropwise to adjust the pH of the aqueous phase to 5.0-7.0 to obtain a dispersion. Vinyl chloride monomer, ester-containing monomer, carboxyl-containing monomer and initiator are added sequentially to the dispersion, wherein the ester-containing monomer accounts for 5-15 mol% of the total molar amount of monomers, the carboxyl-containing monomer accounts for 1-5% of the total molar amount of monomers, and the remainder is vinyl chloride monomer. The amount of initiator is 0.05-0.5 mol% of the total mass of monomers. Under stirring conditions, the suspension polymerization reaction is carried out at 55-65°C for 6-10 hours. After the reaction was completed, the product underwent degassing, centrifugal washing, and fluidized bed drying processes in sequence to obtain the modified polyvinyl chloride functional filler.
2. The method for modifying polyvinyl chloride functional fillers according to claim 1, characterized in that, The inorganic acid is hydrochloric acid; the ester-containing monomer is vinyl acetate or butyl acrylate; the carboxyl-containing monomer is methacrylic acid or acrylic acid; and the initiator is diisopropyl peroxide.
3. The method for modifying polyvinyl chloride functional fillers according to claim 1, characterized in that, In the molecular chain of the modified polyvinyl chloride functional filler, the molar content of carboxyl groups is 1-5 mol, and the molar content of ester groups is 5-15 mol; the average particle size of the modified polyvinyl chloride functional filler is 50-150 μm.
4. The method for modifying polyvinyl chloride functional fillers according to claim 1, characterized in that, The modification method further includes the step of compounding the modified polyvinyl chloride functional filler with a rubber matrix: Solid multifunctional epoxy resin and the first part of the friction performance modifier were premixed at a mass ratio of 1:(1-3) at a speed of 500-1500 rpm to obtain powdered bridging masterbatch. The rubber matrix is subjected to roll plasticizing treatment on an open rubber mixing mill. The modified polyvinyl chloride functional filler, the second part of the friction performance modifier and the powdered bridging masterbatch are added in sequence for mixing and pre-activation treatment. After the filler is evenly dispersed, the vulcanization crosslinking system and epoxy ring-opening catalyst are added. The mixing temperature is controlled between 80-100℃, and the mixture is sheeted to obtain the compound rubber. The compounded rubber is placed in a mold for hot-press cross-linking molding, which causes the rubber matrix to vulcanize. The active groups in the modified polyvinyl chloride functional filler undergo cross-linking reaction with the rubber matrix and / or the interpenetrating network bridging system composed of the solid multifunctional epoxy resin and the epoxy ring-opening catalyst to construct a chemical interpenetrating network structure, thereby obtaining a friction pad. The friction pads are subjected to post-vulcanization and heat preservation treatment to obtain a rubber-based wet friction material based on a modified polyvinyl chloride interpenetrating network structure; wherein, the friction performance modifier includes fiber reinforcement material and mineral filler; the first part of the friction performance modifier is a portion of the mineral filler, accounting for 15%-30% of the total mineral filler mass; the second part of the friction performance modifier is the fiber reinforcement material and the remaining mineral filler.
5. The method for modifying polyvinyl chloride functional fillers according to claim 4, characterized in that, The premixing treatment is carried out in a high-speed mixer; the hot-press cross-linking molding treatment is performed at 150-180℃ and 10-20MPa for 5-15 minutes; the post-vulcanization heat preservation treatment is performed at 160℃ for 2-4 hours.
6. The method for modifying polyvinyl chloride functional fillers according to claim 4, characterized in that, By weight, the compound comprises the following components: the rubber matrix: 100 parts; the modified polyvinyl chloride functional filler: 15-45 parts; The vulcanization crosslinking system: 3-8 parts; Interpenetrating network bridging system: 2-6 parts, wherein the interpenetrating network bridging system is composed of the solid multifunctional epoxy resin and the epoxy ring-opening catalyst in a mass ratio of (10-20):1; Friction performance modifier: 40-80 parts, wherein the friction performance modifier is composed of the first part of the friction performance modifier and the second part of the friction performance modifier.
7. The method for modifying polyvinyl chloride functional fillers according to claim 6, characterized in that, The rubber matrix is nitrile rubber or carboxylated nitrile rubber; the vulcanization crosslinking system contains sulfur, rubber accelerator and zinc oxide.
8. The method for modifying polyvinyl chloride functional fillers according to claim 6, characterized in that, The solid multifunctional epoxy resin is a solid bisphenol A type epoxy resin or an o-cresol formaldehyde type epoxy resin; the epoxy ring-opening catalyst is an imidazole derivative or a quaternary ammonium salt.